FINANCIAL PERFORMANCE ANALYSIS OF BALO'TA SAVINGS AND LOAN COOPERATIVE - Shindika, Shindika; Todingbua, Manuel A; Paridi, Andryanus (Indonesian Journal Of Economy Studies, 2024)
This study aims to analyze the financial performance of Balota Savings and Loan Cooperative over a four-year period (2020-2023). The evaluation is based on key financial ratios, focusing on liquidity, profitability, solvency, and activity to assess the financial health and sustainability of the cooperative. The financial data used in this analysis were collected from the annual financial reports of Balo’ta Savings and Loan Cooperative, including the balance sheet and income statement. The findings indicate that the cooperative maintains a solid liquidity position but faces challenges in profitability due to increasing operating costs and decreasing interest income. In terms of solvency, the cooperative remains stable, but there is a significant decline in its return on equity (ROE) and net profit margin. The study recommends that BSLC adopt stricter cost management practices, diversify its loan portfolio, and explore alternative sources of income to improve its financial performance and long-term growth prospects. This study provides valuable insights for cooperative managers, financial analysts, and policymakers to make informed decisions regarding the cooperative’s financial strategy and future sustainability.Keyword: Financial performance, Balota Savings and Loan Cooperative, liquidity, profitability, solvency, activity, financial ratios, cooperative management, financial sustainability